The relationship of a clinical protocol and emergency treatment success of dental trauma - Susimara Braga de Almeida; Denise Piotto Leonardi; Flávia Sens Fagundes Tomazinho; Beatriz Serrato Coelho; Allan Fernando Giovanini; Eduardo Pizzato; Flares Baratto-Filho (Revista Sul-Brasileira de Odontologia, 2014)
The aim of this study was to investigate whether the sequelae arising from dental trauma in permanent teeth were influenced by the use or non-use of a clinical protocol, in emergency care treatment facilities in the city of Joinville/SC, Brazil. Material and methods: From 2008 to 2010, a total of 70 dental records were reviewed and evaluated 6 months after the completion of treatment. In addition to the data relating to gender, age, etiology, most affected teeth, and most prevalent traumas, the individuals were divided into 2 groups to compare the sequelae observed following either the use or non-use of a clinical protocol for dental trauma treatment. Results: There was a greater incidence of male patients, particularly in the agerange of 8 to 15 years. Falls were the most frequent cause of trauma. The total success rate of the emergency care was of 78.57%. In the group in which the protocol was used, the success rate reached 88.89% compared to 60.0% in the group in which the protocol was not used. Conclusion: The use of a clinical protocol positively influenced the sequelae arising after treatment for dental trauma.